Flora and fauna diversity in Selangkau forest: A basis for developing management plan of cement industrial complex in East Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Aminatun T, Suwasono RA, Putri RA. 2021. Flora and fauna diversity in Selangkau forest: A basis for developing management plan of cement industrial complex in East Kalimantan, Indonesia. Biodiversitas 22: 4555-4565. The management of natural resources for economic development often clashes with environmental protection. That is the case in East Kutai District, East Kalimantan, Indonesia which is faced with competing interests between the development of the cement industry and biodiversity conservation. This study is aimed to identify the diversity of flora and fauna in a forest ecosystem to be developed as a cement industrial complex in the Selangkau Village, Kaliorang Sub-district, East Kutai District, and to provide recommendations for environmental management plans as part of the conservation efforts. A vegetation survey using purposive sampling was performed at four vegetation stages: seedlings, saplings, poles and trees. Analysis was done to examine the diversity, dominance, evenness, richness and importance value indices.  The fauna study was conducted by the exploration method to collect data on mammals, birds, amphibians and reptiles. The vegetation study recorded 29 species including Buchanania arborescens Blume which had the highest importance value in all growth stages.  One species of tree (Shorea glauca) found in this area is also classified as endangered species with high conservation importance. The fauna study found 42 species of birds, 7 of which are protected, 14 species of mammals, 5 of which are protected and 11 species of amphibians and reptiles. Efforts to save the protected species are necessary in response to the new cement factory construction plan in the study area, for example by reclamation and revegetation using the native plants recorded in this study and by transferring animal species into a new habitat that resembles the initial one.
Keywords: biodiversity; ecosystem; exploration; forest; Kalimantan